Competenze, assi culturali e discipline. Un'esperienza di progettazione didattica a Monteroni d'Arbia: brevi note - Emanuela Caione (Firenze University Press, 2013)
The development of a literacy about Skills Approach in education involves a general re-thinking of education, in relation to epochal challenges, to a more active and participatory citizenship and to a knowledge linked to people's existential needs and professional too. This work is to assume that skill/competence as a model in education is possible, and it becomes even desirable. Skills become an instrument for the effective exercise of citizenship rights and contribute to enhance the student's ability to make informed and independent choices in many contexts. This paper has three goals: placing the meaning of skill/competence in education, favoring the interpretation of international and local law about lifelong learning, promoting an integration among skills, knowledge and school matters. A training experience aimed to Italian teachers further demonstrates how organ- ize, promote and practice these integrations: so the school is not passive of new social inquiry but is an active lead of cultural change associated with 'skills'.